Purulent Pericarditis after Liver Abscess: A Case Report - María Fidalgo García; Juan Carlos Rodríguez Sanjuán; María Riaño Molleda; Marta González Andaluz; Hector Real Noval; Manuel Gómez Fleitas (Case Reports in Medicine)
We present the case of a 49-year-old woman, with previous clinical antecedents of recent hepatic metastasis, who was admitted to the ICU due to respiratory failure and hemodynamic instability. She was found to have purulent pericarditis complicated by pericardial tamponade and pleural effusion, as well as surgical site infection, which was the origin of the disease. Cultures of the surgical wound and the pericardial effusion were positive for Enterococcus faecalis and Escherichia coli. A pericardial tap was performed and the intra-abdominal abscess was surgically drained. Pleural effusion was also evacuated. She received antibiotic treatment and recovered successfully. The only after-effect was a well-tolerated effusive-constrictive pericarditis.